English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

the question is on the home page of my website. I couldn't get the text to come out right on here. Thanks in advance.

www.yosmo.com
Note this is for qestion number 5

2006-12-17 16:12:56 · 8 answers · asked by shaykosmo06 1 in Science & Mathematics Mathematics

8 answers

it is (-3x^2)^3

2 x 1
--------------- + --------------
x+1 x-1
2x(x-1)+1(x+1)/(x^2-1)
2x^2-2x+x+1/(x^2-1)
2x^2-x+1/(x^2-1)




Yahoo answers question #2
Solve

2 1 5
--------------- + -------------- = --------
z 2 2z
(4+z)/2z=5/2z
4+z=5
z=1


Yahoo answers question #3
Solve

5x 3

--------------- - -------------- = 4
x+1 x+1
5x-3=4(x+1)
5x-3=4x+4
x=7

2006-12-17 16:15:25 · answer #1 · answered by raj 7 · 0 1

simplify

cubed root of negative 27x ^6

-27 = -3^3

(-3^3 * x^6)^(1/3) (* means multiply)

mulitply the exponents

-3^1 * x^2

so you get -3x^2

2006-12-18 00:17:49 · answer #2 · answered by VZ 2 · 0 0

Your problem was cbrt(-27x^6). That is equal to:

cbrt(-27) * cbrt(x^6) = -3 * (x^6)^(1/3) = -3*(x^(6*(1/3)) = -3*(x^(6/3)) = -3*x^2.

2006-12-18 00:17:14 · answer #3 · answered by alnitaka 4 · 0 0

cubed root of negative 27x ^6

I think it is -3x^2

2006-12-18 00:27:30 · answer #4 · answered by Tony T 4 · 0 0

cubed root of negative 27x ^6

(-27x^6)
= -3x-3x-3. (x^2)^3

Cube root of (-27x^6)
= -3.x^2
= -3x^2

2006-12-18 00:18:29 · answer #5 · answered by Sheen 4 · 0 0

(-27x^6)^(1/3) = [(-27)^(1/3)] * [(x^6)^(1/3)]
= -3 * x^[6*(1/3)] = -3 * x^2 = -3x^2

2006-12-18 00:21:31 · answer #6 · answered by Northstar 7 · 0 0

the answer is 4

2006-12-18 00:14:50 · answer #7 · answered by USMCstingray 7 · 0 0

-9xsquared

2006-12-18 00:15:31 · answer #8 · answered by Curtis G 1 · 0 0

fedest.com, questions and answers